A composite material with controllable electromagnetic characteristics for the terahertz frequency range - Moseenkov, Sergey I.; Dorofeev, Igor O.; Dorozhkin, Kirill V.; Sankova, Natalya; Zavorin, Alexey; Serkova, Alexandra; Parkhomchuk, Ekaterina; Suslyaev, Valentin I.; Kuznetsov, Vladimir L. (Journal of applied physics)
In this study, a new method is proposed for producing polymer composites via the adsorption of multiwalled carbon nanotubes (MWCNTs) on the surface of polystyrene spheres (PS) to provide a cellular distribution of MWCNTs in the composite. The method makes it possible to control the cell size down to the submicron level and the conductivity of the composite in a wide range. The effect of the MWCNT concentration on the surface of PS on the structure of the resulting composites and their electrophysical properties are studied in the frequency range of 115 GHz-1.4 THz. The percolation nature of the composite conductivity was established. It was shown that the obtained composite is a regularly chaotic medium, and its regularity scale corresponds to the sizes of the PS. MWCNTs on the PS surface form two subsystems: the first is a pseudo-regular subsystem on the edges of cuboid-like PS, while the second subsystem consists of chaotically scattered MWCNTs with unclosed ends on the faces of PS. The first subsystem belongs to the regular part of the structure and mainly determines the properties of the medium at frequencies above 500 GHz. The second subsystem of nanotubes is characterized by a small electrodynamic scale comparable with the size of one PS cell and determines the effective properties of the composites at frequencies below 500 GHz. Published under an exclusive license by AIP Publishing.